ISSP 1998 - Religion II: Sweden - Svallfors, Stefan (Umeå University, 2009)
This survey is the Swedish part of the 1998 'International Social Survey Program'. ISSP is an ongoing program of cross-national collaboration. Formed in 1984, the group develops topical modules dealing with important areas of social science as supplements to regular national surveys. The topic of 1998 was 'Religion'.

In this survey the respondents had to give their opinions on different kinds of sexual relations; abortion; people living together without being married; and women working outside of home. The respondents were also asked about their believes about God, and if they believed in heaven, hell or religious miracles. They also had to describe their feelings about the Bible and answer questions about the meaning of life. A number of questions concerned the respondent's religious upbringing: religious preference of the parents, religion raised in, church attendance of parents and church attendance of the respondent in the age of 11-12. Questions about the present religious activities touched upon how often the respondent prays, takes part in religious activities, and how religious she/he consider herself/himself to be. Other questions dealt with voluntary activites; confidence in different authorities and organizations; trust in people; religion vs. modern science; religious leaders right to interfere in elections and government decisions. Socio-economic background information include occupation, trade union affiliation, education, housing, income, marital status, spouse´s occupation, income, number of children, citizenship of parents, and political preferences.

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 1998 investigating Religion.

Detta är den svenska studien inom det internationella forskningsprojektet ISSP. Temat för studien 1998 är ”Religion”. Detta är andra gången studien genomförs på det här temat och har sedan genomförts ytterligare en gång på samma tema (SND 0867).

International Social Survey Program, ISSP, är ett globalt forskningsprojekt som har till uppgift att konstruera och genomföra internationellt jämförbara attitydstudier. Sedan 1985 har attityddata årligen samlats in och utgör nu en databas som är fritt tillgänglig för forskarsamhället. I dagsläget är 48 länder, från sex olika världsdelar, involverade i projektet. Genom bredden av medlemsländer skapas möjlighet till jämförelser i flera dimensioner. Det finns möjligheter att både jämföra länder som har en likartad samhällsstruktur och historia, och länder som skiljer sig påtagligt från varandra.

Sverige har varit medlem i ISSP sedan 1992 och det är Sociologiska intuitionen vid Umeå universitet som är huvudman för studierna i Sverige.

Sedan starten 1985 har attityder från flera olika områden undersökts. Vissa områden har återkommit genom åren, vilket gör det möjligt att även jämföra dem över tid.

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. Studien för 1998 undersöker åsikter om religion.
ISSP 1998 - Åsikter om religion
Keywords: religion; religion; ethics; etik; religious attendance; religiöst deltagande; families; familjer; gender role; könsroll; CORS; CORS; Gender and gender roles; Kön och könsroller; Family life and marriage; Familjeliv och äktenskap; Religion and values; Religion och värderingar; Social Sciences; Samhällsvetenskap; Sociology; Sociologi